Absence of an Optimal Capital Structure in the Famous Tradeoff Theory! - Brusov, P.N.; Filatova, T.V.; Orekhova, N.P. (Journal of Reviews on Global Economics, 2013)
Abstract: Within modern theory of capital structure and capital cost by Brusov-Filatova-Orekhova the analysis of wide known tradeoff theory has been made. It is shown that suggestion of risky debt financing (and growing credit rate near the bankruptcy) in opposite to waiting result does not lead to growing of weighted average cost of capital, WACC, which still decreases with leverage. This means the absence of minimum in the dependence of WACC on leverage as well as the absence of maximum in the dependence of company capitalization on leverage. Thus, it seems that the optimal capital structure is absent in famous tradeoff theory. The explanation to this fact has been done.